Benign Mesenchymal Stromal Cells in Human Sarcomas - Morozov, Alexei (2010)
PURPOSE: Recent evidence suggests that at least some sarcomas arise through aberrant differentiation of mesenchymal stromal cells (MSCs), but MSCs have never been isolated directly from human sarcoma specimens. EXPERIMENTAL DESIGN: We examined human sarcoma cell lines and primary adherent cultures derived from human sarcoma surgical samples for features of MSCs. We further characterized primary cultures as either benign or malignant by the presence of tumor-defining genetic lesions and tumor formation in immunocompromised mice. RESULTS: We show that a dedifferentiated liposarcoma cell line DDLS8817 demonstrates fat, bone and cartilage trilineage differentiation potential characteristic of MSCs. Primary sarcoma cultures have the morphology, surface immunophenotype and differentiation potential characteristic of MSCs. Surprisingly, many of these cultures are benign as they do not form tumors in mice and lack sarcoma-defining genetic lesions. Consistent with the recently proposed pericyte origin of MSCs in normal human tissues, sarcoma-derived benign MSCs express markers of pericytes and cooperate with endothelial cells in tube formation assays. In human sarcoma specimens, a subset of CD146-positive microvascular pericytes express CD105, an MSC marker, while malignant cells largely do not. In an in vitro co-culture model, sarcoma-derived benign MSCs as well as normal human pericytes markedly stimulate the growth of sarcoma cell lines. CONCLUSIONS: Sarcoma-derived benign MSCs/pericytes represent a previously undescribed stromal cell type in sarcoma which may contribute to tumor formation.